Investigation of articulation features in organ pipe sound - B. KOSTEK; A. CZYŻEWSKI (Archives of Acoustics, 2014)
The aim of the paper is to approach the problem of existing limitations in the articulation of sound in a pipe instrument with electromagnetic action. The importance of attack transients in articulation phenomena is examined. Hence, detailed investigations in the domain of attack transients in pipe sound were carried out. The applied methods and the results of analyses are discussed.